Comparative effects of SGLT2 inhibitors and incretin-based therapies on dementia risk in type 2 diabetes: a systematic review and meta-analysis - Song, Kirim; Choi, Jiwon; Jeong, Dayeon; Shin, Dongyun; Ah, Young-Mi; Lee, Ki Young; Choi, Kyung Hee (Frontiers in Endocrinology, 2025)
BackgroundAntidiabetic drugs lower blood glucose levels and may also have neuroprotective and vascular protection effects. In particular, sodium–glucose cotransporter 2 inhibitors (SGLT2is) and incretin mimetics have demonstrated dementia-reducing effects. We evaluated whether SGLT2is reduce dementia risk compared with incretin mimetics in patients with type 2 diabetes (T2D).MethodsSystematic review and meta-analysis were performed by searching the PubMed, Embase, and Cochrane Library databases through February 2025. Both randomized trials and cohort studies were identified and qualitatively assessed, but only cohort studies were included in the quantitative meta-analysis. We also compared the effects of SGLT2is with those of dipeptidyl peptidase-4 inhibitors (DPP-4i) or glucagon-like peptide-1 receptor agonists (GLP-1RA) on dementia incidence.ResultsNine studies were identified for analysis. Compared with incretin mimetics, SGLT2is significantly reduced the overall dementia risk [hazard ratio (HR) 0.82, 95% CI: 0.73-0.91], and SGLT2is had stronger effects than DPP-4i (HR 0.67, 95% CI: 0.59-0.77) and GLP-1RA (HR 0.93, 95% CI: 0.86-1.00). SGLT2i also reduced the risks of vascular dementia and Alzheimer’s disease (HR 0.49, 95% CI: 0.35–0.70 vs. HR 0.68, 95% CI: 0.52–0.88, respectively). The results of subgroup analyses revealed increased benefits for patients aged older than 65 years. Empagliflozin was the most consistently protective among the SGLT2i agents.ConclusionSGLT2is may provide neuroprotective benefits beyond glycemic control in patients with T2D, particularly in older populations at higher risk of cognitive decline. These findings support consideration of SGLT2is as a preferred therapeutic option for patients with T2D at increased risk of dementia, although randomized controlled trials would further strengthen this evidence base.Systematic Review Registrationhttps://www.crd.york.ac.uk/prospero/display_record.php?ID=CRD42024567890 identifier PROSPERO (CRD420251037959).